New criterion for "stability of sight" when shooting with a pneumatic gun on the basis of electronic shooting training system "SCATT" - Ivanov, I. (Research in Kinesiology, 2017)
Stabilometric resistance of the body in this examination has been evaluated through a platform for the examination of equilibrium resistance whose working algorithm is described in Gikova & Tishinov (2013).Simultaneously with the fluctuations of the GCG, the trajectory of sight at shot has been recorded through electronic shooting training system "SCATT", Russia. Our ex-amination showed a direct link between sagittal hesitations of the GCG and vertical thrill of the sight when shooting "straight" with pneumatic gun. The goal of this examination was to seek and define a new quantitative criterion to assess this relationship. A quanti-tative criterion has been proposed as well for "stability of sight" on the ground of on an analysis of the shooting through electronic shooting training system "SCATT", Russia. The obtained results are useful in selecting and training of young shooters as well as for the verification and improvement of sports technique of the experienced marksmen.